Inventory Decisions and Signals of Demand Uncertainty to Investors - Lai, Guoming; Xiao, Wenqiang (Manufacturing and Service Operations Management, 2018)
This paper examines how managerial short-termism can affect a firm’s inventory decision when external investors have only partial information about the firm’s demand uncertainty. We first study the scenario where the manager’s short-termism is exogenously given. We derive the full equilibrium spectrum ranging from stable separating to pooling equilibria, which yields insights for learning firms’ demand uncertainty from their inventory and sales information and for understanding the effect of managerial short-termism on firm performance. We then analyze the scenario where the manager’s short-termism is endogenous. We find that, unlike the scenario with exogenous short-termism, the first-best inventory decisions might be achieved in equilibrium on the basis of an alternative signal. This paper has been accepted for the Manufacturing & Service Operations Management Special Issue on Interface of Finance, Operations, and Risk Management.